2009
DOI: 10.1128/aem.02458-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Characterization of Campylobacter spp. Isolated from Wild Bird Populations in Northern England

Abstract: Campylobacter infections have been reported at prevalences ranging from 2 to 50% in a range of wild bird species, although there have been few studies that have investigated the molecular epidemiology of Campylobacter spp. Consequently, whether wild birds are a source of infection in humans or domestic livestock or are mainly recipients of domestic animal strains and whether separate cycles of infection occur remain unknown. To address these questions, serial cross-sectional surveys of wild bird populations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 51 publications
(88 reference statements)
2
33
3
Order By: Relevance
“…In particular, ST-220 and ST-2209, detected in our study four and five times, respectively, have been associated with pigeons (32). Only one strain belonged to a different MLST profile: ST-45 (CC-45), a genotype distributed widely in terms of hosts and ecologic niche (34) and already described in wild birds (23,33).…”
Section: Discussionmentioning
confidence: 94%
“…In particular, ST-220 and ST-2209, detected in our study four and five times, respectively, have been associated with pigeons (32). Only one strain belonged to a different MLST profile: ST-45 (CC-45), a genotype distributed widely in terms of hosts and ecologic niche (34) and already described in wild birds (23,33).…”
Section: Discussionmentioning
confidence: 94%
“…For example, using culturing techniques, Whelan et al (35) reported that two-thirds of the herring gulls (Larus argentatus) tested were positive to Campylobacter spp., with C. laridis as the dominant species (55%), followed by C. jejuni (30%) and C. coli (15%). In contrast, out of 13 fecal strains tested, Hughes et al (17) identified one strain as C. lari and no C. jejuni or C. coli strains in black-headed gulls (Larus ridibundus) using different functional and ribosomal-gene (i.e., 16 and 23S rRNA gene) PCR assays. Based on previous culture estimations, Campylobacter has been estimated to range from 3.0 ϫ10 3 to 1.7 ϫ 10 7 CFU/g (wet weight) in the ring-billed gull (L. delawarensis) droppings (22), with lower estimates from herring gull and common black-headed gull (L. ridibundus) excreta (1.8 ϫ10 2 to 4.9 ϫ 10 6 CFU/g and from 7.4 ϫ 10 2 to 1.7 ϫ 10 5 CFU/g, respectively) (9).…”
mentioning
confidence: 99%
“…are widespread in the environment, members of this genus are ecologically diverse, clinical cases are sporadic, and associated outbreaks are rare. These factors make epidemiology and source tracking challenging (19,20,29,69). To date, a variety of methods have been used to identify Campylobacter isolates to the species level.…”
mentioning
confidence: 99%